Semantics : from meaning to text - Melʹčuk, Igorʹ A. (Igorʹ Aleksandrovič), 1932- (Studies in language companion series, 2012)
This book presents an innovative and novel approach to linguistic semantics, beginning with the idea that language can be described as a system for the expression of linguistic Meanings as particular surface forms or Texts. Semantics is specifically that system of rules that ensures a correct transition from a Semantic Representation of the Meaning of a family of synonymous sentences to the Deep Syntactic Representation of a particular sentence. Framed in the terms of Meaning-Text linguistics, this volume discusses in detail the problems of Semantic Representation --including the semantic struc.